(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
In this article, the program of measures for the fundamental improvement of personnel policy and the system of state civil services in the republic, the results of the introduced legislation, the nature of the KPI system, the types of KPI system used in world practice, important indicators of efficiency, the urgency of its introduction, the existing KPI system in foreign countries experience, their negative and positive results are analyzed. Also, the need to introduce KPI system in Uzbekistan, the results expected from the introduction, the experience, problems and shortcomings and advantages of the sectors that have introduced this system were tried to be highlighted.